Information systems ethics – challenges and opportunities. Issue 1 (17th October 2017) - Rogerson, Simon; Miller, Keith W.; Winter, Jenifer Sunrise; Larson, David
Abstract : Purpose: The purpose of this paper is to explore the ethical issues surrounding information systems (IS) practice with a view to encouraging greater involvement in this aspect of IS research. Information integrity relies upon the development and operation of computer-based information systems. Those who undertake the planning, development and operation of these information systems have obligations to assure information integrity and overall to contribute to the public good. This ethical dimension of information systems has attracted mixed attention in the IS academic discipline. Design/methodology/approach: The authors are a multidisciplinary team providing a rich, diverse experience which includes professional and information ethics, management information systems, software engineering, data repositories and information systems development. Each author has used this experience to review the IS ethics landscape, which provides four complimentary perspectives. These are synthesised to tease out trends and future pointers. Findings: It is confirmed that there is a serious lack of research being undertaken relating to the ethical dimension of the Information Systems field. There is limited crossover between the well-established multidisciplinary community of Computer Ethics research and the traditional Information Systems research community. Originality/value: An outline framework is offered which could provide an opportunity for rich and valuable dialogue across the two communities. This is proposed as the starting point for a proactive research and practice action plan for information systems ethics.